The Impact of the Administrative Empowerment on Improving Performance: A Case Study of Jordan Telecommunication Company «Orange» - Alzoubi, Mohammad; Alhazaymeh, Ahmad (The Arab Journal of Administration, 2019)
This study has been aimed at explore the impact and importance of administrative empowerment that included: (delegating authority, training, communication methods, and sharing information) on improving job performance of the Jordan Telecommunications Company from viewpoint of its personnel In Jordan within the year 2016. And trying to find out the influences that carry statistical implications at the level (∞ = 0.05 or less) to personal and work variables (I.e., sex, age, experience, educational levels, and marital status). A (155) questionnaire was designed and administered among personnel, a (148) were considered as acceptable. The most important findings of the study were as follows: All variables show that there is a strong statistical significant positive influence at (∞ = 0.05 or less) for employees on organizational performance. Sharing information variable became first, while delegating authority variable became last. The results also show a statistical significant influence at (∞ = 0.05 or less) on organizational performance due to (age, educational level, and martial status) variable, while these significant differences do not appear for (sex, and experience) variable.